The Relationship between Communication Skills and Career Awareness: An Example of Sports Sciences Faculty Students - Veli Ozan Çakır (Journal of Educational Issues, 2024)
The main aim of the research was to determine the relationship between communication skills and career awareness of individuals studying at the faculty of sports sciences. This study was performed according to the relational screening model. The study group of the research consisted of a total of 386 students, 215 males and 171 females, studying at Istanbul University-Cerrahpaşa Faculty of Sports Sciences. In addition to the personal information form in the research, the “Communication Skills Evaluation Scale (CSES)” was developed by Korkut (1996) and the “Career Awareness Scale (CAS)” was developed by Yaşar and Sunay (2019) were used as data collection tools. It was accepted that the research data showed a normal distribution according to the skewness and kurtosis values. After the research data showed normal distribution, t-test, ANOVA and Pearson correlation test were applied in the analysis. In the research results, no significant difference was found between the communication skills of Sport Sciences students according to their gender and grade levels. However, a significant difference was determined between the sub-dimensions of career awareness according to the variables of individuals’ gender and class. As a result of the research, a positive moderate relationship was determined between communication skills and career awareness. Considering that as the communication skills of the students studying at the faculty of sports sciences increase, their career awareness will increase, it is recommended that more studies be conducted to increase the communication skills of the students.